The Effect of Perceived Ease of Use and Perceived Usefulness on Customer Satisfaction Through Customer Trust in the Use of the Brimo Application at Bank BRI - Ageng Taufiq Hidayat; Herma Perdana Prasetyawan; Reza Cahya Dwiputra; Dewi Tamara (Publikasi Indonesia, 2026)
Bank Rakyat Indonesia, through its BRImo application, has become one of the most widely used digital banking platforms in Indonesia. However, technology adoption is influenced not only by system quality but also by users’ perceptions of ease of use, usefulness, trust, and satisfaction. This study aims to examine the effects of Perceived Ease of Use (PEOU) and Perceived Usefulness (PU) on Customer Satisfaction (CS), with Customer Trust (CT) as a mediating variable in BRImo usage. This research employs a quantitative approach with a causal-comparative design and a purposive sampling technique. A total of 460 active BRImo users participated by completing a Likert-scale questionnaire. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The outer model results indicate that all indicators are valid and reliable, while the inner model demonstrates strong coefficients of determination for Customer Trust and Customer Satisfaction. The findings reveal that both PU and PEOU have positive and significant effects on Customer Satisfaction and Customer Trust. Furthermore, Customer Trust significantly influences Customer Satisfaction and mediates the relationships between PU, PEOU, and Customer Satisfaction. These results highlight the importance of perceived benefits, ease of use, and trust in shaping customer satisfaction in digital banking services. Theoretically, this study reinforces the integration of the Technology Acceptance Model with the trust construct. Practically, the findings provide strategic insights for BRI in enhancing the quality of the BRImo application and strengthening the user experience.